Case Report: 18 Year Old Male Patient with Lupus Nephritis - Halim, Kurnia (International Journal of Public Health Excellence (IJPHE), 2024)
Systemic lupus erythematosus is a chronic autoimmune disease that can affect various organs of the body, one of the most commonly affected complications is the kidneys and results in lupus nephritis, the percentage of disease occurrence is more than 50% of patients in the first 5 years. Male patients tend to have more aggressive disease with renal, vascular, and cardiac involvement. Based on the criteria of Systemic Lupus International Collaborating Clinics in 2012 defines lupus nephritis if there is proteinuria in 24 hours ≥ 0.5 g / day, there is urine sediment, and there is a decrease in renal filtration function. Although the disease can be diagnosed based on these three things kidney biopsy remains the gold standard of diagnosis. In this case report, an 18-year-old male with lupus history came to the emergency room with the main complaint of fever accompanied by shortness of breath, from the results of supporting examinations obtained anemia, thrombocytopenia, high creatinine, and eGFR of 4 mL/minute, complete urine showed proteinuria, cylinders, and erythrocytes, AP thorax photos showed cardiomegaly, bronchopneumonia, and bilateral pleural effusions. Based on history, physical examination, lab, and imaging, the patient was diagnosed with systemic lupus erythematosus, lupus nephritis, chronic kidney disease, normocytic normochromic anemia, and community acquired pneumonia. The patient received glucocorticoids, immunosuppressants, diuretic, antihypertensives, antibiotics, and other supportive therapy, The patient also received renal replacement therapy in the form of hemodialysis and a kidney biopsy will be done after the condition improves